Vedolizumab for acute gastrointestinal graft-versus-host disease: A systematic review and meta-analysis - Li, Allen Cheng-Wei; Dong, Chen; Tay, Soon-Tzeh; Ananthakrishnan, Ashwin; Ma, Kevin Sheng-Kai (Frontiers in Immunology, 2022)
Objective: To determine the safety and efficacy of vedolizumab for the prophylaxis and treatment of gastrointestinal involvement of acute graft-versus-host disease (GVHD) (GI-aGVHD). Methods: Literature search within PubMed, EMBASE, Web of Science, and Cochrane Library for observational studies and clinical trials that evaluated the effect of vedolizumab on GI-aGVHD through May 17th, 2022. A bivariate and random-effects meta-analysis derived the pooled observational percentages and pooled risk ratios (RRs) from baseline of primary endpoints including overall or complete response, mortality, and adverse events. Results: There were a total of 122 participants in eight eligible studies, including one study on the prophylactic use of vedolizumab and seven studies on vedolizumab for the treatment of GI-aGVHD. Of seven studies that reported details on baseline grades of GI-aGVHD, a total of 47 patients (47.95%) were of grade IV, 31 patients (31.63%) were of grade III, 10 patients (10.2%) were of grade II, and 10 patients (10.2%) were of grade I. The use of vedolizumab for the treatment of GI-aGVHD yielded significantly improved objective response rate (ORR) at 14 days (pooled ORR=60.53%, pooled RR=14.14, 95%CI: 2.95-67.71), 28 days (pooled ORR=50%, RR=7.36, 95%CI=2.14-25.37), and 12 months (pooled ORR=76.92%, RR=13.66, 95%CI=3.5-53.35) from baseline. Likewise, the use of vedolizumab was followed by a significantly improved complete response (CR) at 12 months (pooled CR=27.27%, RR=5.50, 95%CI=1.01-29.95), yet the CR at 14 days and 28 days did not reach statistical significance. 57 out of 87 (pooled overall survival, OS=34.5%) and 46 out of 65 (pooled OS=29.2%) patients expired at 6 months and at 12 months after the use of vedolizumab, respectively. Prophylactic use of vedolizumab was not associated with any specific type of reported adverse events, while patients with GI-aGVHD on vedolizumab presented with significantly increased risks of adverse events including infections (RR=7.55) and impaired metabolism/nutrient (RR=9.00). All analyses were of a low heterogeneity (all I-squares=0%). Conclusion: Vedolizumab was safe and effective for the prophylaxis and management of early grade GI-aGVHD. More clinical evidence is warranted to validate these findings.